Estimation of Costunolide and Dehydrocostus Lactone in Saussurea lappa and its Polyherbal Formulations followed by their Stability Studies Using HPLC-DAD - Rao Vadaparthi, P.R. (Pharmacogn Mag, 2015)
BACKGROUND: Saussurea lappa is one of the popular Ayurvedic herb; costunolide and dehydrocostus lactones are well-known sesquiterpene lactones contained in many plants used as popular herbs, such as S. lappa, and have been considered as potential candidates for the treatment of various types of tumor. OBJECTIVE: The present study was used for the quantification of costunolide and dehydrocostus lactone in S. lappa and its polyherbal formulations, stability studies of markers and characterization of their degradants. MATERIALS AND METHODS: HPLC analysis was performed on Waters NOVAPAK HR C(18) column (300 mm × 3.9 mm i.d., 6 μm) using isocratic elution with acetonitrile and water (60:40% v/v). RESULTS: The calibration curves of both analytes showed good linearity within the established range 5-100 μg/ml. The limits of detection (LOD) and quantification (LOQ) were 1.5 and 4.6 μg/ml for costunolide and 1.3 and 4.0 μg/ml for dehydrocostus lactone, respectively. Good results were achieved with respect to repeatability (%RSD < 2.0) and recovery (99.3-101.8%). CONCLUSION: The method was found to be precise, accurate, specific, and was successfully used for analyzing costunolide and dehydrocostus lactone in S. lappa and its polyherbal formulations. The developed method was found to be suitable for stability studies of markers and characterization of their degradation products.